Slower carriers limit charge generation in organic semiconductor light-harvesting systems - Ardalan Armin (Nature Communications, 2016)
Blends of electron donating and accepting organic semiconductors are widely used as photoactive materials in next generation solar cells and photodetectors. The yield of free charges in these systems is often determined by the separation of interfacial electron-hole pairs, which is expected to depend on the ability of the faster carrier to escape the Coulomb potential. Here we show, by measuring geminate and non-geminate losses and key transport parameters in a series of bulk-heterojunction solar cells, that the charge-generation yield increases with increasing slower carrier mobility. This is in direct contrast with the well-established Braun model where the dissociation rate is proportional to the mobility sum, and recent models that underscore the importance of fullerene aggregation for coherent electron propagation. The behavior is attributed to the restriction of opposite charges to different phases, and to an entropic contribution that favors the joint separation of both charge carriers.